Microbiome disturbance and resilience dynamics of the upper respiratory tract during influenza A virus infection - Drishti Kaul (Nature Portfolio, 2020)
Influenza A virus (IAV) infection can be exacerbated by bacterial co-infections but the effect of IAV on the upper respiratory tract (URT) microbiome remains unclear. Here, the authors compare the dynamics of the UTR microbiome in IAV-infected ferrets and humans, finding similar trends at the ecosystem and individual taxon level in both hosts.